2012
DOI: 10.1097/olq.0b013e31824cbecc
|View full text |Cite
|
Sign up to set email alerts
|

Urethritis/Cervicitis Pathogen Prevalence and Associated Risk Factors Among Asymptomatic HIV-Infected Patients in South Africa

Abstract: Asymptomatic urethritis/cervicitis pathogens were highly prevalent in this population. Few urethritis/cervicitis pathogen-associated patient characteristics were identified, emphasizing the need for affordable STI diagnostics to screen HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 14 publications
5
32
0
Order By: Relevance
“…Because syndromic management relies on self-reported symptoms and clinical examination for visible signs, it is often unsuccessful at detecting asymptomatic infections. Fortunately, this study identified a low number of asymptomatic infections and none was primarily gonococcal or chlamydial infection, as usually reported (7). …”
Section: Discussionsupporting
confidence: 63%
“…Because syndromic management relies on self-reported symptoms and clinical examination for visible signs, it is often unsuccessful at detecting asymptomatic infections. Fortunately, this study identified a low number of asymptomatic infections and none was primarily gonococcal or chlamydial infection, as usually reported (7). …”
Section: Discussionsupporting
confidence: 63%
“…One possible explanation for this gender difference may be that women are more likely to receive care in community or Provincial clinics that were not captured in our data. The difference is more likely due to high rates of asymptomatic STIs among women [20] resulting in a higher prevalence of clinic visits among men. We also found that younger patients were more likely to have STI, a finding that is consistent with the broader pattern of STI outside of people living with HIV [21].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with several other studies which also found higher percentage of asymptomatic STIs in HIV positive individuals. [5][6][7][8] Thus the strategy of syndromic management works well in the HIV negative individuals where a very small percentage of patients who are actually infected but asymptomatic are missed. However in case of the HIV positive individuals the percentage of asymptomatic STIs is quite high and in this group the approach of syndromic management misses out large number of HIV positive asymptomatic patients who are actually infected with RTIs/STIs and remain untreated and are responsible for silently transmitting these infections in the community.…”
Section: Discussionmentioning
confidence: 99%